Streptomyces Derived Nano-doxorubicin: Clinical Status and Patents Granted - Kaur, Prabhjot; Bhandari, Divya Dhawal; Chopra, Hitesh (Scripta Medica, 2024)
Streptomyces have been presented as a great source of antibiotics and anti-cancer drugs over the past century. Especially Streptomyces living in adverse conditions produce certain metabolites with cytolytic and anti-microbial activities, which have been utilised for manufacturing antimicrobial and anticancer drugs. Doxorubicin (DOX) is a potent anti-cancer drug derived from Streptomyces, that is widely used for various cancers, including cancers of the ovary, urinary bladder, GI tract, breast, thyroid gland, lung, bone, kidney (nephroblastoma) and blood (leukaemia). This anthracycline antibiotic is limited by its adverse effect profile, with the main adverse effects being nausea, vomiting, alopecia, infertility, cardiotoxicity, myelosuppression and nephrotoxicity. Nanoparticle delivery systems present a good solution to avoid adverse effects. Some nano-based formulations have reached the clinics, while many new ones in the pipeline show promising results. This review attempts to compile the existing literature on the clinical status of DOX highlight the need for the development of nanoparticles (NPs) that may serve as drug delivery agents, imaging probes and other multifunctional particulates. The integration of nanotechnology with Streptomyces-derived compounds can help shape the anti-cancer therapy of the future.